2010
DOI: 10.1115/1.3177451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compression on the Water Management of a Proton Exchange Membrane Fuel Cell With Different Gas Diffusion Layers

Abstract: The gas diffusion layer (GDL) plays an important role in maintaining suitable water management in a proton exchange membrane fuel cell. The properties of the gas diffusion layer, such as its porosity, permeability, wettability, and thickness, are affected by the shoulders of the bipolar plates due to the compression applied in the assembly process. Compression therefore influences the water management inside fuel cells. A two-phase fuel cell model was used to study the water management problem in a proton exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…There exists a transitional region, that is, a nonlinear porosity distribution zone in the GDL region corresponding to the interface between the channel and the shoulders, a linear porosity distribution zone above the shoulders, and a constant porosity distribution zone above the middle part of the channels for the cases when an assembly pressure is applied. A similar nonlinear porosity distribution zone caused by the compression was also found in most of the available GDL models . Unfortunately, the impact of such nonlinear porosity distributions in the GDL has not been well investigated in the literature.…”
Section: Numerical Results and Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…There exists a transitional region, that is, a nonlinear porosity distribution zone in the GDL region corresponding to the interface between the channel and the shoulders, a linear porosity distribution zone above the shoulders, and a constant porosity distribution zone above the middle part of the channels for the cases when an assembly pressure is applied. A similar nonlinear porosity distribution zone caused by the compression was also found in most of the available GDL models . Unfortunately, the impact of such nonlinear porosity distributions in the GDL has not been well investigated in the literature.…”
Section: Numerical Results and Discussionsupporting
confidence: 64%
“…Non‐linear deformations of the GDL under various assembly pressures were obtained in the numerical work; however, the properties of the non‐linear porosity distribution were not implemented in the CFD investigations . A remarkable numerical work was presented by Shi et al , who investigated water management under inhomogeneous compression coinciding with the calculated non‐linear porosity. That study reported that the presence of liquid water could result in a non‐uniform distribution of the porosity and permeability in the GDL.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly though, is its role to evenly distribute the reactants to the reaction sites and to provide water management [24,25]. This explains the use of porous material in the design of the GDL; the void area provides a region for the free diffusion of gaseous species and the removal of the reaction products, while the solid is used as a transport medium for the electrons to and from the reaction site.…”
Section: Carbon Paper Gas Diffusion Layermentioning
confidence: 99%
“…Higher compression decreases the contact resistance between the GDL and the plates (FFP) 5, 8–11, however, it also decreases the porosity and transport ability 4, 12, 13. This has been studied mathematically and experimentally 14–16.…”
Section: Introductionmentioning
confidence: 99%